Epidemiology and Molecular Study of Schistosoma haematobium Infection Among People in Riverine Communities of Sokoto State, Nigeria - Jafaru, Suleiman; Isyaku, Nike Tawakaltu; Ukatu, Victoria Ebere; Bagudo, Ahmad Ibrahim (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Microscopic examination of urine samples from individuals has long been regarded as the gold standard for diagnosing Schistosoma haematobium infection in Nigeria. However, the reliability of this method has been questioned. In light of this, the present study was designed to conduct an Epidemiology and Molecular Study of S. haematobium Infection Among People in Riverine Communities of Sokoto State. A total of 900 urine samples were collected. These samples underwent microscopic examination after filtration. Positive samples underwent DNA extraction, followed by PCR analysis to detect the presence of Schistosoma haematobium at 121 base pairs. Microscopically, 315 out of 900 samples (35.0%) tested positive for Schistosoma haematobium, with a mean egg intensity of 45.3 eggs per 10 mL of urine. The prevalence was notably high among fishermen (57.1%), individuals using any available water source (100.0%), visitors to freshwater bodies (37.7%), those residing very close to freshwater bodies (41.5%), and individuals who urinated indiscriminately (70.0%). The intensity of infection was significantly elevated among housewives (56.5%), visitors to freshwater bodies (58.7%), and individuals who urinated directly into freshwater bodies (57.2%). PCR analysis further confirmed the presence of Schistosoma haematobium in 87.6% of the samples previously analyzed microscopically. Infection rates were particularly significant among fishermen (98.2%), individuals using rivers as their water source (99.1%), visitors to freshwater bodies (89.8%), swimmers (97.8%), those residing very close to freshwater bodies (98.6%), and individuals who urinated directly into freshwater bodies (98.9%). The study revealed that microscopic examination alone may not be entirely effective in the study area. Therefore, the adoption of binary diagnosis methods is strongly recommended for more efficient detection of Schistosoma haematobium in the State.